Ligand Decorated Embelin Loaded PLGA Nanoparticles for Management of Alcohol Induced Hepatotoxicity - Kumar, Ajay; Khan, M. Nikhat; Kanoujia, Jovita; Singh, Amandeep; Mishra, Neeraj (Journal of Drug Delivery and Therapeutics, 2020)
Preparation of surface modified Embelin loaded nanoparticles (GA-PEG-PLGA) for the management of hepatotoxicity. Surface modified Embelin loaded GA-PEG-PLGA NPs were evaluated by NMR, FTIR, TEM techniques and in vitro release studies. The biodistribution of the nanoparticles was assessed by High-performance liquid chromatography (HPLC), and the cellular uptake study was evaluated using Hep G2 cells (liver cells lines). The hepatoprotecttive effect of the surface modified Embelin loaded GA-PEG-PLGA NPs was investigated in-vitro and in-vivo. The surface modified Embelin loaded GA-PEG-PLGA nanoparticles significantly increases the uptake of drug in liver by 2.5 folds more than plain drug.Keywords: Glycyrrhetinic acid, Receptor mediated, Surface functionalization, Embelin, PLGA nanoparticle.